Role of carbon taxes in adjusting to global warming. - Pearce, David (1991)
Argues that notwithstanding the dispute over possible effects, a fairly aggressive policy stance is merited and carbon taxes have a number of features to commend them. In particular they do not distort incentives, and by generating revenue they facilitate reductions in other incentive-distorting taxes. The disadvantages of the carbon tax are not seen as being so serious as to rule out the tax as an option.